2021
DOI: 10.1088/1361-6463/ac3e90
|View full text |Cite
|
Sign up to set email alerts
|

Ferrimagnetic–ferromagnetic phase transition in Mn4N films favored by non-magnetic In doping

Abstract: The ferrimagnet Mn4N forms a family of compounds useful in spintronics. In a compound comprising non-magnetic and magnetic elements, one basically expects the compound to become ferromagnetic when the proportion of the magnetic element increases. Conversely, one does not expect ferromagnetism when the proportion of the non-magnetic element increases. Surprisingly, Mn4N becomes ferromagnetic at room temperature when the Mn content is decreased by the addition of In atoms, a non-magnetic element. X-ray magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…There are two sites on which Mn can be replaced by doping, 1a or 3c. Co tends to replace Mn at the 3c site and Fe, Cr and In have little preference [11,12]. Zhang et al showed that Ga occupies 1a corner positions in the bulk material [6].…”
Section: Magnetic and Magneto-transport Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two sites on which Mn can be replaced by doping, 1a or 3c. Co tends to replace Mn at the 3c site and Fe, Cr and In have little preference [11,12]. Zhang et al showed that Ga occupies 1a corner positions in the bulk material [6].…”
Section: Magnetic and Magneto-transport Propertiesmentioning
confidence: 99%
“…No compensation is found for Z = Cr and Fe because these dopant atoms occupy both corner and face-centered sites with no particular preference [11]. In the case of In substitution, a ferrimagnetic-ferromagnetic phase transition was reported between x = 0.15 and x = 0.27 based on AHE measurements and first principles calculations [12]. There has also been a recent study by Sakaguchi et al on the transport and optical properties of boron doped Mn 4 N thin films, where the boron atoms occupy interstitial sites at the center of the unit cell [13].…”
Section: Introductionmentioning
confidence: 99%
“…Various magnetic phases have been discovered in antiperovskite-type magnetic materials with combinations of light elements and host metals. For example, Fe 4 N, Mn 2 Co 2 C, [177] and Mn 3 GaC [178] are ferromagnets, Mn 4 N and derivatives with transition metal doping are ferrimagnets, [179][180][181][182] and Mn 3 XN compounds [183] are antiferromagnets, where X denotes transition metals such as Ni, Zi, and Cu. Ferromagnets and ferrimagnets have traditionally been employed for classical spintronic applications such as magnetic memories as well as magnetic sensors.…”
Section: Antiferromagnetic Nitridesmentioning
confidence: 99%